2005
DOI: 10.1111/j.1365-2044.2004.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of drotrecogin alfa (activated) for the treatment of severe sepsis in the United Kingdom*

Abstract: SummaryDrotrecogin alfa (activated) is licensed in Europe for the treatment of severe sepsis in patients with multiple organ failure. We constructed a model to assess the cost effectiveness of drotrecogin alfa (activated) from the perspective of the UK National Health Service when used in adult intensive care units. Patient outcomes from a 28-day international clinical trial (PROWESS) and a subsequent follow-up study (EVBI) were supplemented with UK data. Cost effectiveness was assessed as incremental cost per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…73 The remaining 15 studies evaluated the cost-effectiveness of other health-care interventions for the treatment of severe sepsis and septic shock. [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Five published abstracts were also identified; however, only limited information on the methods employed was reported and so these studies were excluded from the final literature review. A flow chart of studies included in the final costeffectiveness review is shown in Figure 35.…”
Section: Results Of the Cost-effectiveness Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…73 The remaining 15 studies evaluated the cost-effectiveness of other health-care interventions for the treatment of severe sepsis and septic shock. [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Five published abstracts were also identified; however, only limited information on the methods employed was reported and so these studies were excluded from the final literature review. A flow chart of studies included in the final costeffectiveness review is shown in Figure 35.…”
Section: Results Of the Cost-effectiveness Literature Reviewmentioning
confidence: 99%
“…87 Eleven of the 15 studies reported results in terms of the incremental cost per QALY gained. 74,75,77,[80][81][82][83][84][85][86]88,89 The perspective assumed by each of the studies is also reported in Table 17. The majority of studies considered the perspective of the providing institution (hospital) or of the health-care sector more generally.…”
Section: Cost-effectiveness Of Non-intravenous Immunoglobulin Intervementioning
confidence: 99%
See 2 more Smart Citations
“…Economic evaluations in several countries including the United Kingdom, France, Germany, Sweden, the United States, and Canada [30][31][32][33][34][35][36][37] show that APC is cost effective, on a short-term basis, in severe sepsis. Further, when APC is administered, according to the PROWESS criteria, to individuals with more severe disease (APACHE II score ≥25), it has a lifetime cost-effectiveness profile that compares well to that of many widely accepted therapies [33,35].…”
Section: Discussionmentioning
confidence: 99%